Condition Based Railway Pantograph Dynamic Behavior Measurement and Fault Diagnosis. Issue 24 (2018) - Xin, T.; Roberts, C.; Weston, P.; Stewart, E.
Abstract: Railway pantographs are used for collecting power from the overhead line system. Faults or failures of a pantograph will degrade the interaction between the pantograph and the overhead line, reducing the reliability of railway operation. The current pantograph maintenance techniques are highly dependent on visual and manual checks, which are not efficient. To improve pantograph maintenance efficiency and reduce the maintenance budget, a laboratory based pantograph test rig is developed to measure pantograph dynamic behaviors through different tests and develop a quick pantograph fault diagnosis method. Based on the test rig and the measurement result, pantograph 3D multibody and lumped mass models are established. Three tests are carried out: hysteresis measurement using different excitation speeds, frequency response function with various excitation levels, and a novel changing gradient test. The measurement data collected from a new pantograph is considered as the reference. Differences between the dynamic behaviors measured on a test pantograph and the reference data indicate faults or component degradation. The results indicate that the hysteresis test is effective in detecting pneumatic actuator and elbow joint issues; the frequency response function can monitor all faults, but it is time consuming; the changing gradient test is a quick way to identify and locate the fault.